Wolność akademicka jako zawód i powołanie - Godek-Ostrouch, Lidia (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2021)
Academic Freedom as a Profession and Vocation is an attempt to give an updated reading of Weber’s category of the vocation of science through the lens of academic freedom. This is the first such attempt; until now, the interplay between the two has not been explored in the literature. The paper begins by posing a question: how should we understand the role of academic freedom and to what extent should it be respected in scientific practice and science policy-making? We can analyse academic freedom on two different levels: (a) the methodological level relating to the principles of constructing scientific knowledge (perspectivism, conceptual constructivism, problematization); and (b) the practical level, including the postulate of academic freedom understood as a founding assumption of modern science. The dual perspective on academic freedom can also be seen in the Weberian category of science as vocation. I argue that academic freedom is the normative standard for the ideal of vocation: it is a necessary condition for the project of vocation (understood as an ethical ideal), and above all, freedom is a co-evident parameter of thinking at the level of cognitive operations and human cognitive action choices (the cognitive ideal). Moreover, I attempt to explore the extent to which Weber’s concept of academic freedom can help us understand our problems with academic freedom today. It is difficult to overestimate the importance of academic freedom for the work of academics as well as the democratic ecosystem as a whole. Weber’s notion of academic freedom has important implications for the crafting of institutional support for responsible science in the twenty-first century – implications that have yet to be fully grasped, much less implemented.
Wolność akademicka jako zawód i powołanie jest próbą aktualizacyjnego odczytania Weberowskiej kategorii powołania nauki przez pryzmat wolności akademickiej. Jest to pierwsza taka próba, do tej pory w literaturze przedmiotu nie badano wzajemnych relacji pomiędzy nimi. Publikacja rozpoczyna się od postawienia pytania: jak powinniśmy rozumieć rolę wolności akademickiej i do jakiego stopnia jej wymogi powinny być respektowane w praktyce naukowej i kształtowaniu polityki naukowej? Wolność akademicką możemy analizować na dwóch różnych poziomach: (a) poziomie metodologicznym, który uwzględnia zasady konstruowania wiedzy naukowej (perspektywizm, konstruktywizm pojęciowy, problematyzacja); oraz (b) poziomie praktycznym, który obejmuje postulat wolności akademickiej rozumiany jako założenie współczesnej nauki. Dwoistą perspektywę wolności akademickiej można również dostrzec w Weberowskiej kategorii nauki jako powołania. Argumentuję, że wolność akademicka jest normatywnym standardem ideału powołania: jest warunkiem koniecznym projektu powołania (rozumianego jako ideał etyczny), a nade wszystko wolność jest współistotnym parametrem myślenia na poziomie operacji poznawczych i wyborów ludzkiego działania poznawczego (rozumianego jako ideał poznawczy). Ponadto próbuję zbadać, na ile Weberowska koncepcja wolności akademickiej może pomóc nam w zrozumieniu naszych problemów z wolnością akademicką dzisiaj. Trudno przecenić znaczenie wolności akademickiej dla pracy zarówno naukowców, jak i całego ekosystemu demokratycznego. Weberowska koncepcja wolności akademickiej ma ważne implikacje dla tworzenia instytucjonalnego wsparcia dla odpowiedzialnej nauki w XXI wieku, które nie zostały jeszcze w pełni zrozumiane, a tym bardziej wdrożone.
Keywords: academic freedom; science as a profession and vocation; science policy; democracy; wolność akademicka; nauka jako zawód i powołanie; polityka naukowa; demokracja